The expression profiles of circular RNAs and competing endogenous RNA networks in intrahepatic cholangiocarcinoma - Liang, Zi; Liu, Liyan; Guo, Xinyi; Wu, Xia; Yu, Yun-Li; Yu, Ziyang; Hu, Xiaolong; Zhang, Xing; Wang, Ji (Frontiers in Cell and Developmental Biology, 2022)
Introduction: Intrahepatic cholangiocarcinoma (iCCA) is a heterogeneous entity with diverse etiologies, morphologies and clinical outcomes, but our knowledge of its epidemiology and carcinogenesis is very limited. Materials & methods: The expression patterns of circRNAs were explored in iCCA tissues and corresponding adjacent normal ones, denoted by (iCCA) and (iCCAP), respectively, using high-throughput sequencing. Results: A total of 117 DE circRNAs were identified. Based on the parental transcripts of circRNAs, these DE circRNAs were related with important GO terms and were enriched in important pathways. Two circRNA mediated ceRNA netwoks were constructed and many important immunity and metabolic pathways related to mRNAs were regulated by DE circRNAs via miRNAs. Conclusion: Our study revealed the DE circRNAs in the iCCA tissues compared with iCCAP ones, suggesting that circRNAs may play crucial roles in the pathogenesis of iCCA.